MYBL2 alternative splicing-related genetic variants reduce the risk of triple-negative breast cancer in the Chinese population - Chen, Xinyu; Feng, Jin; Zhang, Yuan; Liu, Jiarui; Zhang, Lijia; Zeng, Pu; Wen, Langbo; Wang, Xin; Zhang, Yi (Frontiers in Genetics, 2023)
Background: Triple-negative breast cancer (TNBC) is the most malignant subtype of breast cancer, and studies have found an association between MYB proto-oncogene like 2 (MYBL2) and TNBC development; however, the specific mechanisms underlying this development remain unknown. Recent studies have reported the association of alternative splicing (AS) with cancer, providing new approaches to elucidate the carcinogenesis mechanism. This study aimed to identify MYBL2 AS-related genetic variants that influence the risk of developing TNBC. Methods: We conducted a case-control study of 217 patients with TNBC and 401 cancer-free controls. The CancerSplicingQTL database and HSF software were used to screen for MYBL2 AS-related genetic variants. The association of sample genotypes with the risk of TNBC development and with clinicopathological features were analyzed via unconditional logistic regression. Results: Two AS-associated SNPs, rs285170 and rs405660, were identified using bioinformatics analysis. Logistic regression analysis showed that both rs285170 (OR = 0.541; 95% CI = 0.343–0.852; p = 0.008) and rs405660 (OR = 0.642; 95% CI = 0.469–0.879; p = 0.006) exhibited protective effects against TNBC under the additive model. Stratification analysis showed that these two SNPs had more significant protective effects in the Chinese population aged ≥ 50 years. Additionally, we found that rs405660 was associated with the risk of lymph node metastasis (OR = 0.396, 95% CI = 0.209–0.750, p = 0.005) in TNBC. Conclusion: We found for the first time that MYBL2 AS-related genetic variants are associated with reduced TNBC susceptibility in the Chinese population, especially in women aged ≥ 50 years.